Mechanical and acoustic characteristics of oxidized, nitrided and oxynitrided Zr-1%Nb zirconium alloy - Trush, V.S.; Pylypenko, M.M.; Stoev, P.I.; Lavrys, S.M.; Kravchyshyn, T.M.; Luk’yanenko, O.H.; Tikhonovsky, M.A. (Вопросы атомной науки и техники, 2022)
The effect of the gaseous medium composition during thermo-chemical treatment (TCT) on the mechanical properties and acoustic parameters of Zr-1%Nb zirconium alloy was studied. It is shown that TCT in oxygen-nitrogen contained gaseous media significantly increases the surface hardness and does not worsen the mechanical characteristics (including their plasticity) of zirconium alloy which is used as a material for case of fuel nuclear rod. It is established that TCT in different mediums also influences on acoustic parameters of the Zr-1%Nb alloy. Noticeable changes in the acoustic parameters observed at the initial stage of deformation are associated with the features of the destruction of a thin film formed on the zirconium alloy surface after TCT. Наведено дані щодо впливу складу газового середовища, в якому проводили хіміко-термічну обробку (ХТО), на механічні властивості та акустичні параметри зразків із сплаву цирконію Zr-1%Nb. Показано, що ХТО за вибраними режимами в кисневмісному, азотовмісному та азотокисневмісному газових середовищах суттєво збільшує твердість поверхневого шару зразків сплаву цирконію та не погіршує механічні характеристики зразків твельних оболонок, у тому числі їх пластичність. Показано, що за впливом середовища ХТО на характеристики сплаву акустичні параметри виявилися більш інформативними порівняно з механічними властивостями. Зроблено припущення, що помітні зміни акустичних параметрів, що спостерігаються на початковій стадії деформування, пов’язані з особливостями руйнування тонкої плівки, що утворюється на поверхні трубки в результаті ХТО.